Hubungan lama hemodialisis dengan nafsu makan dan status gizi pada pasien penyakit ginjal kronis - Dian Dian; Taufiq Firdaus Al Ghifari Atmadja; Ai Sri Kosnayani (Jurnal SAGO Gizi dan Kesehatan, 2023)
Background: Hemodialysis is an alternative therapy to replace kidney function for people with Chronic Kidney Disease (CKD). Proper dialysis procedures must be maintained to maintain nutritional balance. Failure in the dialysis procedure results in loss of nutrients in the dialysate, which can increase catabolism and acid reflux.Objectives: This study aims to analyze the relationship between the length of hemodialysis and appetite and the nutritional status of CKD patients receiving hemodialysis therapy twice a week at UPTDK RSUD Dr. Soekardjo City of Tasikmalaya in 2023.Methods: The research design used cross-sectional with consecutive sampling, namely as many as 69 CKD patients undergoing hemodialysis—statistical analysis using a chi-square test.Results: Most of the respondents (73,9%) had been on hemodialysis for a long time (≥24 months), most of the respondents (76,8%) had less appetite, and the majority of respondents (78,3%) were malnourished. The results of the correlation test showed that there was a relationship between the length of hemodialysis with appetite (p = 0,022 and OR = 4,3; 95% CI = 1,298-14,240) and nutritional status (p = 0,000 and OR = 11,5; 3, 103-42,621).Conclusion: Length of hemodialysis in patients with CKD has a significant relationship with appetite and nutritional status